THE CONVOLUTION OPERATION ON THE DUAL SPACE TO THE ALGEBRA C(P*(X)) - Василишин, Тарас Васильович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
We define and prove the correctness of the convolution operation on the dual space to the Fréchet algebra C( P * ( X ) ) , which is the completion of the algebra of all continuous ∗ -polynomials on a complex Banach space X with respect to the metric, generated by the system of uniform norms on closed balls of the space X .